Binder composition for electrodes, its manufacturing method, and coating liquid composition for electrodes
Patent Information
- Application Number
- JP2022196642
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-12-08
- Publication Date
- 2025-02-13
- Estimated Expiration
- 2042-12-08
AI Technical Summary
【0009】 本発明の電極用バインダー組成物を用いることにより、電極を形成するための塗工液の固形分濃度を高くしても粘度上昇を抑制することができるので、本発明の電極用バインダー組成物は、固形分濃度の高い電極形成用塗工液を調製するために適したものである。
Smart Images

Figure 0007629436000001 
Figure 0007629436000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode binder composition, an electrode coating liquid composition, an electrode for an electricity storage device, an electricity storage device, and a method for producing the electrode binder composition. [Background technology]
[0002] Secondary batteries, such as lithium secondary batteries, are indispensable driving power sources for various electronic devices, automobiles, etc., and are widely used in the industrial sector, with active research and development being conducted at present. Since the characteristics of a battery are greatly influenced by the types of materials that compose the battery, in recent years, active development has been conducted to improve the performance of electrodes.
[0003] It is known that such electrodes are formed by, for example, applying a coating liquid containing an electrode active material, an electrode binder, a dispersant, and the like to a current collector. In particular, the electrode characteristics of a battery electrode are determined by the electrode active material and the current collector, but the binder also plays an important role in determining the electrode characteristics. From this perspective, it is considered important to improve the binder characteristics. For example, Patent Document 1 discloses a technology for imparting excellent cycle characteristics and rate characteristics to an electricity storage device by using an electrode using an electrode binder composition containing a urethane resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-097906 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, when attempting to form an electrode using an electrode binder containing a conventional urethane resin, increasing the solids concentration of the coating liquid used to form the electrode increases the viscosity, which has been problematic in that it leads to reduced dispersibility and reduced workability.
[0006] The present invention has been made in view of the above, and aims to provide an electrode binder composition that can suppress an increase in viscosity even when the solid content concentration of a coating liquid for forming an electrode is increased, a method for producing the same, and an electrode coating liquid composition containing the binder composition. Another aim of the present invention is to provide an electrode for a power storage device and a power storage device formed using the electrode coating liquid composition. [Means for solving the problem]
[0007] As a result of extensive research into achieving the above object, the present inventors have discovered that the above object can be achieved by using a polyurethane resin having a specific particle size distribution, and have thus completed the present invention.
[0008] That is, the present invention includes, for example, the subject matter described in the following sections. Item 1 A binder composition for electrodes comprising an aqueous dispersion of a polyurethane resin, The polyurethane resin has a D50 volume average particle diameter of 0.01 μm or more and 0.05 μm or less, and a D90 volume average particle diameter of 0.10 μm or more and 0.15 μm or less. Section 2 Item 2. The electrode binder composition according to item 1, comprising carbon nanotubes. Section 3 Item 3. The electrode binder composition according to item 2, comprising carboxymethyl cellulose or a salt thereof. Section 4 Item 4. A coating liquid composition for an electrode, comprising the binder composition for an electrode according to any one of Items 1 to 3. Section 5 Item 5. An electrode for a power storage device, comprising the solid content of the electrode coating liquid composition according to item 4. Section 6 Item 6. An electricity storage device comprising the electricity storage device electrode according to item 5. Section 7-1 A method for producing an electrode binder composition containing an aqueous polyurethane resin dispersion, comprising the steps of: A method for producing a binder composition for an electrode, comprising the step of preparing an aqueous dispersion of a polyurethane resin having a D50 volume average particle diameter of 0.01 μm or more and 0.05 μm or less and a D90 volume average particle diameter of 0.10 μm or more and 0.15 μm or less. Section 7-2 A method for producing the binder composition according to any one of items 1 to 3, A method for producing a binder composition for an electrode, comprising the step of preparing an aqueous dispersion of a polyurethane resin having a D50 volume average particle diameter of 0.01 μm or more and 0.05 μm or less and a D90 volume average particle diameter of 0.10 μm or more and 0.15 μm or less. Effect of the Invention
[0009] By using the electrode binder composition of the present invention, an increase in viscosity can be suppressed even if the solids concentration of a coating liquid for forming an electrode is increased. Therefore, the electrode binder composition of the present invention is suitable for preparing a coating liquid for forming an electrode having a high solids concentration. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, embodiments of the present invention will be described in detail. In this specification, the expressions "containing" and "comprise" include the concepts of "containing", "comprises", "consists essentially of" and "consists only of".
[0011] 1. Electrode binder composition The present invention encompasses an electrode binder composition. The electrode binder composition includes an aqueous dispersion of a polyurethane resin, and the polyurethane resin has a D50 volume average particle diameter of 0.01 μm or more and 0.05 μm or less and a D90 volume average particle diameter of 0.10 μm or more and 0.15 μm or less. That is, the electrode binder composition of the present invention contains an aqueous dispersion of a polyurethane resin having a specific particle size distribution.
[0012] By including such a polyurethane resin in the electrode binder composition of the present invention, when the electrode binder composition of the present invention is applied to a coating liquid for forming an electrode, an increase in viscosity of the coating liquid can be suppressed. In particular, even if the solid content of the coating liquid is high, an increase in viscosity can be suppressed. Therefore, the electrode binder composition of the present invention is suitable for preparing a coating liquid with a high solid content, and is suitable as a binder component (binding agent) of an electrode coating liquid composition used for producing an electrode for an electricity storage device.
[0013] In this case, the coating liquid refers to a coating liquid containing an electrode active material, an electrode binder, a dispersant, etc., and used to form an electrode, and in particular refers to the electrode coating liquid composition of the present invention described below.
[0014] (Polyurethane resin water dispersion) The polyurethane resin water dispersion is a dispersion of a polyurethane resin in an aqueous medium. The type of polyurethane resin contained in the polyurethane resin water dispersion is not particularly limited as long as it has the above particle size distribution, and may be, for example, a wide variety of known polyurethane resins.
[0015] For example, the polyurethane resin can be formed from the following components (A) and (B), and may contain one or both of components (C) and (D) as necessary. In other words, the polyurethane resin has structural units based on components (A) and (B), and has one or both of structural units based on components (C) and (D) as necessary. Component (A): a compound having two or more isocyanate groups, (B) component: a compound having two or more active hydrogen groups, (C) component: a compound having one or more active hydrogen groups and a hydrophilic group; Component (D): Chain extender
[0016] Examples of component (A) (a compound having two or more isocyanate groups) include a wide variety of known isocyanate compounds, such as bifunctional isocyanate compounds such as aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, and araliphatic diisocyanates.
[0017] Examples of the aliphatic diisocyanate include tetramethylene diisocyanate, dodecamethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2-methylpentane-1,5-diisocyanate, 3-methylpentane-1,5-diisocyanate, etc. Examples of the alicyclic diisocyanate include isophorone diisocyanate, hydrogenated xylylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, methylcyclohexylene diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, etc. Examples of aromatic diisocyanates include tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 4,4'-dibenzyl diisocyanate, 1,5-naphthylene diisocyanate, xylylene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, etc. Examples of aromatic aliphatic diisocyanates include dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, α,α,α,α-tetramethylxylylene diisocyanate, etc.
[0018] As the component (A), an isocyanate compound having three or more isocyanate groups can be used in place of or in combination with the bifunctional isocyanate compound.
[0019] The (A) component preferably contains 80% by mass or more of the bifunctional isocyanate compound, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 95% by mass or more. The (A) component may be only the bifunctional isocyanate compound. The (A) component may be one type alone or two or more types.
[0020] Component (A) can be produced by a known method, or can be obtained commercially.
[0021] Examples of component (B) (a compound having two or more active hydrogen groups) include compounds having two or more hydroxyl groups, two or more amino groups, or two or more mercapto groups at the molecular end or within the molecule, and specific examples include known polyethers, polyesters, polyetheresters, polycarbonates, polythioethers, polyacetals, polyolefins, polysiloxanes, fluorine-based compounds, vegetable oil-based compounds, etc. Component (B) may not have a carboxy group, and may not have a sulfonic acid group.
[0022] As the component (B), a compound having two or more hydroxyl groups and / or a polyol compound, etc. Examples of the compound having two or more hydroxyl groups include ethylene glycol, propylene glycol, propanediol, butanediol, pentanediol, 3-methyl-1,5-pentanediol, hexanediol, neopentyl glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, dipropylene glycol, tripropylene glycol, 1,4-cyclohexanedimethanol, bisphenol A, bisphenol F, bisphenol S, hydrogenated bisphenol A, dibromobisphenol A, 1,4-cyclohexanedimethanol, dihydroxyethyl terephthalate, and hydroquinone dihydroxyethyl ether.
[0023] Examples of the polyol compound include known polycarbonate polyols, polycaprolactone polyols, polyester polyols, polythioether polyols, polyacetal polyols, polytetramethylene glycols, polybutadiene polyols, polyisoprene polyols, polychloroprene polyols, and the like.
[0024] The polycarbonate polyol is not particularly limited, and may be a wide variety of known polycarbonate polyols, such as 1,6-hexanediol carbonate polyol, 1,4-butanediol and 1,6-hexanediol carbonate polyol, 1,5-pentanediol and 1,6-hexanediol carbonate polyol, 3-methyl-1,5-pentanediol and 1,6-hexanediol carbonate polyol, etc.
[0025] In order to introduce a branched structure into the polyurethane resin, the component (B) preferably contains a compound having three or more active hydrogen groups reactive with an isocyanate group, such as a polyhydric alcohol, such as trimethylolpropane, glycerin, or pentaerythritol, or an oxyalkylene derivative thereof.
[0026] Additionally, component (B) may contain a short-chain low molecular weight diol such as ethylene glycol, 1,4-butanediol, 1,4-cyclohexanedimethanol, etc., in order to localize the urethane bonds within the polyurethane.
[0027] Component (B) can be produced by a known method, or can be obtained as a commercially available product.
[0028] Component (C) (a compound having one or more active hydrogen groups and a hydrophilic group) is a compound other than components (A) and (B). For example, component (C) is a compound other than a polyol compound.
[0029] In the (C) component, the hydrophilic group may be any of anionic hydrophilic groups, cationic hydrophilic groups, and nonionic hydrophilic groups. Examples of the anionic hydrophilic group include a carboxyl group and its salts, and a sulfonic acid group and its salts. Examples of the cationic hydrophilic group include a tertiary ammonium salt and a quaternary ammonium salt. Examples of the nonionic hydrophilic group include a group consisting of a repeating unit of ethylene oxide, and a group consisting of a repeating unit of ethylene oxide and a repeating unit of another alkylene oxide.
[0030] Specific examples of component (C) include compounds having one or more active hydrogen groups and one or more carboxy groups (or salts thereof), compounds having one or more active hydrogen groups and one or more sulfonic acid groups (or salts thereof), compounds having one or more active hydrogen groups and one or more tertiary ammonium salts, compounds having one or more active hydrogen groups and one or more quaternary ammonium salts, and compounds having one or more active hydrogen groups and one or more nonionic hydrophilic groups.
[0031] Examples of compounds containing one or more active hydrogen groups and one or more carboxy groups (or salts thereof) include 2,2-dimethylolpropionic acid, 2,2-dimethylolbutyric acid, 2,2-dimethylolvaleric acid, dioxymaleic acid, 2,6-dioxybenzoic acid, 3,4-diaminobenzoic acid, and other carboxylic acid-containing compounds, their derivatives, and their salts, and also include polyester polyols obtained using carboxylic acid-containing compounds.Other examples of compounds containing one or more active hydrogen groups and one or more carboxy groups (or salts thereof) include amino acids such as alanine, aminobutyric acid, aminocaproic acid, glycine, glutamic acid, aspartic acid, and histidine, and carboxylic acids such as succinic acid, adipic acid, maleic anhydride, phthalic acid, and trimellitic anhydride.
[0032] Examples of the compound having one or more active hydrogen groups and one or more sulfonic acid groups (or salts thereof) include sulfonic acid-containing compounds such as 2-oxyethanesulfonic acid, phenolsulfonic acid, sulfobenzoic acid, sulfosuccinic acid, 5-sulfoisophthalic acid, sulfanilic acid, 1,3-phenylenediamine-4,6-disulfonic acid, and 2,4-diaminotoluene-5-sulfonic acid, and derivatives thereof. Also included are polyester polyols, polyamide polyols, and polyamide polyester polyols obtained by copolymerizing two or more of the above sulfonic acid-containing compounds.
[0033] The compound having one or more active hydrogen groups and one or more carboxy groups (or salts thereof) and the compound having one or more active hydrogen groups and one or more sulfonic acid groups (or salts thereof) may be a salt in which the carboxy group or sulfonic acid group is neutralized with a neutralizing agent. This improves the dispersibility of the polyurethane resin in water. Examples of the neutralizing agent include non-volatile bases such as sodium hydroxide and potassium hydroxide, tertiary amines such as trimethylamine, triethylamine, dimethylethanolamine, methyldiethanolamine, and triethanolamine, and volatile bases such as ammonia.
[0034] Examples of the compound containing one or more active hydrogen groups and a tertiary ammonium salt include alkanolamines such as methylaminoethanol and methyldiethanolamine. The tertiary ammonium salt may be a salt neutralized by a neutralizing agent. This improves the dispersibility of the polyurethane resin in water. Examples of the neutralizing agent include organic carboxylic acids such as formic acid and acetic acid, hydrochloric acid, and sulfuric acid. From the viewpoint of ease of emulsification, the compound containing one or more active hydrogen groups and a tertiary ammonium salt is preferably methyldiethanolamine neutralized with an organic carboxylic acid. Neutralization may be performed at any stage before, during, or after the formation of the urethane resin.
[0035] Examples of the compound having one or more active hydrogen groups and a quaternary ammonium salt include compounds obtained by quaternizing alkanolamines such as the above-mentioned methylaminoethanol and methyldiethanolamine with alkyl halides such as methyl chloride and methyl bromide, and dialkyl sulfates such as dimethyl sulfate. From the viewpoint of ease of emulsification, the compound having one or more active hydrogen groups and a quaternary ammonium salt is preferably a compound obtained by quaternizing methyldiethanolamine with dimethyl sulfate or the like.
[0036] The compound having at least one each of active hydrogen group and nonionic hydrophilic group is not particularly limited, and is preferably a compound containing at least 30% by mass of ethylene oxide repeating units and having a number average molecular weight of 300 to 20000. Examples of such compounds include nonionic group-containing compounds such as polyoxyethylene glycol, polyoxyethylene-polyoxypropylene copolymer glycol, polyoxyethylene-polyoxybutylene copolymer glycol, polyoxyethylene-polyoxyalkylene copolymer glycol or monoalkyl ethers thereof, or polyester polyether polyols obtained by copolymerizing these.
[0037] The component (C) is preferably a compound containing at least one active hydrogen group and at least one carboxyl group, in which case the electrode binder composition of the present invention is more likely to have improved adhesion to the current collector.
[0038] When the component (C) is an anionic hydrophilic group-containing compound, the polyurethane resin preferably has an acid value, which indicates the content of anionic hydrophilic groups, of 5 to 50 mgKOH / g, and more preferably 5 to 45 mgKOH / g, in terms of being easily excellent in dispersibility. The acid value can be calculated from the number of mg of KOH required to neutralize the free carboxyl groups contained in 1 g of solid content of the polyurethane water dispersion in accordance with JIS K0070-1992. When the component (C) is a nonionic group-containing compound, the content of the nonionic group-containing compound is preferably 1 to 30 parts by mass, more preferably 3 to 25 parts by mass, and even more preferably 5 to 20 parts by mass per 100 parts by mass of the polyurethane resin.
[0039] Component (C) can be produced by a known method, or can be obtained as a commercially available product.
[0040] Examples of the (D) component include a wide variety of chain extenders used in the production of urethane resins. Specific examples of the (D) component include diamine compounds and polyamine compounds. Examples of the diamine compounds include ethylenediamine, trimethylenediamine, piperazine, isophoronediamine, and amino group-containing silane coupling agents, and examples of the polyamine compounds include diethylenetriamine, dipropylenetriamine, and triethylenetetramine. It is also preferable that the (D) component contains a polyamine having three or more functional groups in order to introduce an internal crosslinking structure into the polyurethane and improve the electrolyte resistance.
[0041] The polyurethane resin can have a content ratio of structural units based on component (D) (chain extender) per 100 parts by mass of the polyurethane resin of, for example, 0.1 part by mass or more and 3 parts by mass or less, and preferably 0.2 part by mass or more and 1 part by mass or less.
[0042] The polyurethane resin can be formed only from the constituent units based on the components (A), (B), (C) and (D), and can also contain other constituent units as long as the effects of the present invention are not impaired. The content ratio of the constituent units based on the components (A), (B), (C) and (D) contained in the polyurethane resin is not particularly limited, and can be, for example, the same as that of known polyurethane resins.
[0043] The polyurethane resin preferably has a urethane bond amount of 300 to 20,000 g / eq, and more preferably 400 to 10,000 g / eq, in that flexibility is unlikely to decrease and binding properties are likely to be excellent.
[0044] The number average molecular weight of the polyurethane resin is not particularly limited, and can be, for example, 50,000 or more and 1,000,000 or less, in terms of easiness in forming a coating film. The crosslink density of the polyurethane resin is also not particularly limited, and is preferably, for example, 0.01 to 0.50 per 1,000 molecular weight of the polyurethane resin. The crosslink density of the polyurethane resin can be measured by a known method.
[0045] As described above, the polyurethane resin has a D50 volume average particle diameter of 0.01 μm or more and 0.05 μm or less, and a D90 volume average particle diameter of 0.10 μm or more and 0.15 μm or less. When the polyurethane resin has such a particle size distribution, the electrode binder composition containing the polyurethane resin aqueous dispersion can suppress the increase in viscosity of the coating liquid for forming an electrode, and therefore, even if the solid content concentration of the coating liquid is high, the viscosity is unlikely to increase. Therefore, the electrode binder composition containing the polyurethane resin aqueous dispersion is suitable for preparing a coating liquid with a high solid content concentration, and is suitable as a binder component (binding agent) of an electrode coating liquid composition used to manufacture an electrode for a storage device.
[0046] Here, the D50 volume average particle diameter means the particle diameter at the point where the volume cumulative distribution is 50% in the particle size distribution curve of the polyurethane resin, and the D90 volume average particle diameter means the particle diameter at the point where the volume cumulative distribution is 90% in the particle size distribution curve of the polyurethane resin. The D50 volume average particle diameter and D90 volume average particle diameter (hereinafter simply referred to as "D50" and "D90", respectively) of the polyurethane resin refer to values measured using a dynamic light scattering (DLS) particle size distribution measuring device (Nanotrac WaveII (manufactured by Microtrack Bell)).
[0047] If the D50 of the polyurethane resin in the polyurethane resin water dispersion is less than 0.01 μm, the synthesis method of the polyurethane resin water dispersion becomes extremely complicated or difficult to synthesize. If the D50 of the polyurethane resin in the polyurethane resin water dispersion exceeds 0.05 μm, it becomes difficult to suppress the increase in viscosity of the coating liquid, and as a result, it becomes difficult to increase the solid content concentration of the coating liquid. The D50 of the polyurethane resin in the polyurethane resin water dispersion is preferably 0.015 μm or more, more preferably 0.02 μm or more.
[0048] If the D90 of the polyurethane resin in the polyurethane resin water dispersion is less than 0.10 μm, it is difficult to suppress the increase in viscosity of the coating liquid, and as a result, it is difficult to increase the solid content concentration of the coating liquid. If the D90 of the polyurethane resin in the polyurethane resin water dispersion exceeds 0.15 μm, it is difficult to suppress the increase in viscosity of the coating liquid, and as a result, it is difficult to increase the solid content concentration of the coating liquid. The D90 of the polyurethane resin in the polyurethane resin water dispersion is preferably 0.11 μm or more.
[0049] The method of adjusting the D50 and D90 of the polyurethane resin in the polyurethane resin water dispersion is not particularly limited, and for example, a method of controlling the particle size distribution of the polyurethane resin water dispersion can be widely adopted. Specifically, as described later, in the production of the polyurethane resin water dispersion, it is preferable to adjust the D50 and D90 of the polyurethane resin by controlling the conditions of emulsification dispersion. In addition, the D50 and D90 of the polyurethane resin can also be adjusted by the amount of raw materials ((A) component, (B) component, (C) component, (D) component, and chain extender) used in the production of the polyurethane resin, the proportion of water used, etc.
[0050] In the polyurethane resin aqueous dispersion, the type of the dispersion medium is not particularly limited, and examples thereof include water, lower alcohols having 1 to 3 carbon atoms, and mixed solvents thereof. Among these, the dispersion medium is preferably water from the viewpoint of excellent dispersibility of the polyurethane resin.
[0051] The solid content concentration of the polyurethane resin water dispersion is not particularly limited. From the viewpoint of workability, the solid content concentration of the polyurethane resin water dispersion is preferably 1 mass% or more and 60 mass% or less, more preferably 3 mass% or more and 55 mass% or less, and even more preferably 4 mass% or more and 50 mass% or less.
[0052] (Method for producing aqueous polyurethane resin dispersion) The method for producing the polyurethane resin water dispersion is not particularly limited, and for example, the same method as the known method for producing the polyurethane resin water dispersion can be adopted. For example, the (A) component, the (B) component, and if necessary, the (C) component are mixed to prepare a urethane prepolymer, and the urethane prepolymer is emulsified and dispersed to obtain the polyurethane resin water dispersion. The mixing process can be carried out in a solvent as necessary. It is preferable that such a solvent is inactive to the isocyanate group and has a property capable of dissolving the generated urethane prepolymer. From this viewpoint, examples of the solvent include dioxane, methyl ethyl ketone, dimethylformamide, tetrahydrofuran, N-methyl-2-pyrrolidone, acetone, toluene, dioxane, ethyl acetate, butyl acetate, and propylene glycol monomethyl ether acetate. It is preferable that the solvent used in the reaction is finally removed.
[0053] The temperature of the mixing treatment is not particularly limited, and can be, for example, 30°C to 130°C. The time of the mixing treatment can be appropriately set according to the temperature, and is, for example, 0.5 hours to 10 hours. The reaction between the (A) component and the (B) component proceeds by the mixing treatment, and a urethane prepolymer is generated. When the mixing treatment is performed using a solvent, a urethane prepolymer solution is obtained. After the urethane prepolymer is generated, and before emulsification and dispersion, neutralization of the anionic hydrophilic group of the (C) component, neutralization or quaternization of the cationic hydrophilic group can be performed by a known method, as necessary.
[0054] In the mixing process, the amounts of the (A), (B) and (C) components used are not particularly limited, and for example, the same amounts as those used in known methods can be adopted. For example, the (A) component can be used so that the equivalent ratio of the total amount of active hydrogen groups reactive with isocyanate groups in the (B), (C) and (D) components to the isocyanate groups of the (A) component is 1:0.85 to 1:1.1. The (A) component may be used in a stoichiometric excess amount.
[0055] The method for emulsifying and dispersing the urethane prepolymer obtained by the mixing process is not particularly limited, and a wide variety of known methods can be used. For example, the urethane prepolymer can be emulsified and dispersed by mixing a solution of the urethane prepolymer with alkaline water and applying shear using an emulsifying and dispersing machine such as a homogenizer.
[0056] Examples of the alkaline water used for emulsification and dispersion include aqueous solutions of various alkaline components. Among them, sodium hydroxide is preferable as the alkaline component. That is, the alkaline water is preferably an aqueous sodium hydroxide solution. In this case, the D50 and D90 of the polyurethane resin are easily adjusted to the desired range. In terms of easily adjusting the D50 and D90 of the polyurethane resin to the desired range, the concentration of the alkaline water is, for example, preferably 0.5 to 1 mass%, more preferably 0.6 to 0.9 mass%, and even more preferably 0.65 to 0.85 mass%. The solution of the urethane prepolymer and the alkaline water can be mixed, and then sheared by an emulsification and dispersion machine such as a homogenizer, and then water can be further added.
[0057] The method of mixing the urethane prepolymer solution with alkaline water is not particularly limited, and the D50 and D90 of the polyurethane resin can be appropriately adjusted to be within the desired range. For example, it is preferable to drop alkaline water into the urethane prepolymer solution and mix it. In terms of ease of adjusting the D50 and D90 of the polyurethane resin to be within the desired range, it is preferable to use a urethane prepolymer solution in which the drop amount in terms of the alkaline component (i.e., the drop amount of the alkaline component per minute) is 0.55×10 to 100 parts by mass of the urethane prepolymer. -2 (mass parts / min) or more, 1×10 -2 In the dropping of the alkaline water, the dropping amount in terms of the alkaline component is preferably 0.6×10 to 100 parts by mass of the urethane prepolymer. -2 (parts by mass / min) or more, more preferably 0.65×10 -2 (parts by mass / min) or more, more preferably 0.66×10 -2(parts by mass / min) or more, and preferably 0.95×10 -2 (parts by mass / min) or less, more preferably 0.9×10 -2 (parts by mass / min) or less, more preferably 0.85×10 -2 (parts by mass / minute) or less.
[0058] In terms of ease of adjusting the D50 and D90 of the polyurethane resin to the desired range, it is preferable to drip the alkaline water so that the dripping amount in terms of water (i.e., the dripping amount of water per minute) is 0.6 (parts by mass / min) or more and 5 (parts by mass / min) or less per 100 parts by mass of the urethane prepolymer. The dripping amount of water contained in the alkaline water is more preferably 0.7 (parts by mass / min) or more, even more preferably 0.8 (parts by mass / min) or more, and particularly preferably 0.9 (parts by mass / min) or more per 100 parts by mass of the urethane prepolymer. In addition, the dripping amount of water contained in the alkaline water is more preferably 4 (parts by mass / min) or less, even more preferably 3.5 (parts by mass / min) or less, and particularly preferably 3 (parts by mass / min) or less, per 100 parts by mass of the urethane prepolymer.
[0059] In this specification, the total mass of the urethane prepolymer in the urethane prepolymer solution can be considered to be the same as the total amount of components (A), (B) and (C) used to produce the urethane prepolymer.
[0060] The total mass of the alkaline water and water used for emulsification dispersion is preferably 100 to 900 parts by mass, more preferably 110 to 800 parts by mass, and even more preferably 120 to 700 parts by mass, per 100 parts by mass of the urethane prepolymer, in that this makes it easier for the particle size distribution of the polyurethane resin to fall within the desired range.
[0061] As described above, in the present invention, the D50 and D90 of the polyurethane resin can be easily adjusted to the desired range by adjusting the emulsification and dispersion conditions, particularly the alkaline water used for emulsification and the addition rate thereof.
[0062] The chain extension can be performed by adding the (D) component at the same time as or after the emulsification and dispersion. This generates urea bonds by the interfacial polymerization reaction between the isocyanate groups in the emulsion micelles and the (D) component, which is a chain extender, and improves the crosslinking density in the emulsion micelles, forming a three-dimensional crosslinked structure. Even if the (D) component is not used, the water molecules present in the system can cause chain extension by emulsifying and dispersing the urethane prepolymer in water.
[0063] When component (D) is used, its amount is not particularly limited. For example, the amount of component (D) used can be adjusted so that the equivalent ratio of the isocyanate groups in the urethane prepolymer to component (D) is 1:0.5 to 1:0.9.
[0064] After emulsification and dispersion, the solvent used may be removed as necessary to obtain an aqueous polyurethane dispersion.
[0065] The polyurethane resin aqueous dispersion obtained by the above method has a D50 of 0.01 μm or more and 0.05 μm or less and a D90 of 0.10 μm or more and 0.15 μm or less, and is therefore suitable for the electrode binder composition of the present invention, as described above.
[0066] (Other components contained in the electrode binder composition) The electrode binder composition of the present invention may contain other components in addition to the polyurethane resin aqueous dispersion. The other components are not particularly limited, and may be, for example, the same as those in known electrode binder compositions.
[0067] For example, the electrode binder composition of the present invention may contain carbon nanotubes. The type of carbon nanotubes is not particularly limited, and may be the same as that contained in known electrode binder compositions. Specific examples of carbon nanotubes include single-wall carbon nanotubes (SWCNTs) and multi-wall carbon nanotubes (MWCNTs), and single-wall carbon nanotubes are preferred because they can increase electronic conductivity with a small amount.
[0068] The fiber diameter and fiber length of the carbon nanotubes are not particularly limited, and for example, the number average fiber diameter is preferably 0.5 nm or more and 20 nm or less, and the number average fiber length is preferably 0.5 μm or more and 1 mm or less. By making the number average fiber diameter 0.5 nm or more, it is possible to suppress the viscosity from becoming too high, so that the preparation of the coating composition for electrodes described later is likely to be easy. In addition, by making the number average fiber diameter 20 nm or less, the flexibility is improved, so that the durability when made into a battery is likely to be improved. The number average fiber diameter is more preferably 1 nm or more and 10 nm or less, and even more preferably 2 nm or more and 8 nm or less. In addition, by making the number average fiber length 0.5 μm or more, the durability of the obtained electrode is likely to be improved, and the cycle life of the obtained battery is likely to be improved. By making the number average fiber length 1 mm or less, it is likely to be easy to control the rheology of the carbon nanotubes. The number average fiber length is more preferably 1 μm or more and 10 μm or less, and even more preferably 2 μm or more and 7 μm or less. The number average fiber length and number average fiber diameter can be calculated by measuring the major axis and diameter of 100 carbon nanotubes randomly selected from, for example, a transmission electron micrograph or a scanning probe micrograph, and taking the number average.
[0069] When the electrode binder composition of the present invention contains carbon nanotubes, the content thereof is not particularly limited, and is, for example, preferably 0.1 to 10 parts by mass, and more preferably 0.5 to 5 parts by mass, per 100 parts by mass of the urethane resin.
[0070] When the electrode binder composition of the present invention contains carbon nanotubes, the electrode binder composition of the present invention may also contain a dispersant A. This makes it easier to improve the dispersibility of the carbon nanotubes in the electrode binder composition.
[0071] Examples of the dispersant A include celluloses such as hydroxymethylcellulose, carboxymethylcellulose, and alkali metal salts thereof, methylcellulose, ethylcellulose, hydroxypropylmethylcellulose, and hydroxyethylmethylcellulose. Among them, carboxymethylcellulose or a salt thereof is more preferable. When the electrode binder composition of the present invention contains carboxymethylcellulose or a salt thereof, the dispersibility of carbon nanotubes is further improved. The carboxymethylcellulose or a salt thereof is particularly preferably a sodium salt of carboxymethylcellulose.
[0072] When the electrode binder composition of the present invention contains the dispersant A, the content thereof is not particularly limited, and is, for example, preferably 0.1 to 10 parts by mass, and more preferably 0.2 to 8 parts by mass, per 100 parts by mass of the urethane resin.
[0073] The electrode binder composition of the present invention may further contain various components such as an antioxidant, a light stabilizer, etc. The electrode binder composition of the present invention preferably contains 60% by mass or more of the polyurethane resin aqueous dispersion, more preferably contains 80% by mass or more, further preferably contains 90% by mass or more, and particularly preferably contains 95% by mass or more.
[0074] The method for producing the electrode binder composition of the present invention is not particularly limited. The method for producing the electrode binder composition of the present invention comprises a step of preparing the polyurethane resin aqueous dispersion. That is, the method for producing the electrode binder composition of the present invention comprises a step of preparing a polyurethane resin aqueous dispersion having a D50 volume average particle diameter of 0.01 μm or more and 0.05 μm or less and a D90 volume average particle diameter of 0.10 μm or more and 0.15 μm or less. Such a polyurethane resin aqueous dispersion can be obtained by the above-mentioned method for producing a polyurethane resin aqueous dispersion.
[0075] When the electrode binder composition of the present invention contains carbon nanotubes and / or dispersant A, the electrode binder composition can be prepared, for example, by mixing the electrode binder composition (the polyurethane resin aqueous dispersion) obtained as described above with carbon nanotubes and / or dispersant A. The carbon nanotubes and / or dispersant A can be used in a state of being dispersed or dissolved in a dispersion medium, and in this case, the dispersion medium can be, for example, the same as the dispersion medium of the polyurethane resin aqueous dispersion.
[0076] As described above, the electrode binder composition of the present invention is suitable as a binder component (binding agent) of an electrode coating liquid composition used to manufacture an electrode for a power storage device. In particular, the electrode binder composition of the present invention can suppress an increase in the viscosity of the coating liquid, and can make it difficult for the viscosity to increase even if the solid content concentration of the coating liquid is increased. Therefore, an electrode coating liquid composition containing the electrode binder composition of the present invention makes it possible to form an electrode having excellent performance.
[0077] 2. Electrode Coating Fluid Composition The electrode coating liquid composition of the present invention is not particularly limited in terms of other components contained therein, so long as it contains the electrode binder composition. For example, the electrode coating liquid composition of the present invention may further contain components contained in known electrode coating liquid compositions.
[0078] Specifically, the electrode coating liquid composition of the present invention contains an active material and a conductive assistant in addition to the electrode binder composition, and may further contain a dispersant B and the like as necessary.
[0079] (active material) The active material may be a positive electrode active material or a negative electrode active material, with a negative electrode active material being preferred in that it has improved dispersibility and the viscosity is less likely to increase even when the solid content concentration is increased.
[0080] The positive electrode active material may be a wide variety of known positive electrode active materials, including various positive electrode active materials capable of inserting and desorbing lithium ions. Specific examples include metal oxides such as CuO, Cu2O, MnO2, MoO3, V2O5, and CrO3, composite oxides of lithium and transition metals such as LixCoO2 and LixNiO2, metal chalcogenides, conductive polymer compounds, and the like. Among these, composite oxides of lithium and one or more transition metals such as cobalt, nickel, and manganese, which are generally called high voltage systems, are preferred in terms of their ability to release lithium ions and to easily obtain high voltages.
[0081] The negative electrode active material may be a wide variety of known negative electrode active materials, including various negative electrode active materials capable of inserting / desorbing metallic lithium or lithium ions. Specific examples include carbon materials such as natural graphite, artificial graphite, non-graphitizable carbon, and easily graphitizable carbon; metallic lithium, alloys, and tin compounds; lithium transition metal nitrides; crystalline metal oxides; amorphous metal oxides; silicon compounds; and conductive polymers. Among these, silicon compounds are more preferable, and SiO is even more preferable, because the viscosity is not particularly likely to increase even when the solid content concentration is increased.
[0082] (Conductive assistant) Conductive additives can be broadly classified as electronically conductive materials that do not adversely affect battery performance. For example, in addition to carbon black such as acetylene black and kettin black, conductive materials such as natural graphite (scale graphite, flake graphite, clay graphite, etc.), artificial graphite, carbon whiskers, carbon fibers, metal (copper, nickel, aluminum, silver, gold, etc.) powder, metal fibers, conductive ceramic materials, etc. can be mentioned. In addition, when the electrode binder composition contains carbon nanotubes, the electrode coating liquid composition does not need to contain carbon nanotubes. The conductive assistant contained in the electrode coating liquid composition can be one type or two or more types.
[0083] In the electrode coating liquid composition, the content of the conductive assistant can be the same as that of known electrode coating liquid compositions, and is, for example, preferably 0.1 to 30 mass %, more preferably 0.2 to 20 mass %, based on the active material.
[0084] (Dispersant B) The dispersant B is not particularly limited, and can be a wide variety of dispersants contained in known electrode coating liquid compositions. Specific examples include celluloses such as hydroxymethylcellulose, carboxymethylcellulose, and alkali metal salts thereof, methylcellulose, ethylcellulose, hydroxypropylmethylcellulose, and hydroxyethylmethylcellulose; cellulose nanofibers such as chemically modified cellulose nanofibers; polycarboxylic acid compounds such as polyacrylic acid and sodium polyacrylate; compounds having a vinylpyrrolidone structure such as polyvinylpyrrolidone; and other polymer compounds such as polyester resins, polyacrylamide, polyethylene oxide, polyvinyl alcohol, sodium alginate, xanthan gum, carrageenan, guar gum, agar, and starch. Among them, the dispersant B is preferably a cellulose, and a carboxymethylcellulose salt is particularly suitable. In addition, when the electrode binder composition contains the dispersant A, the electrode coating liquid composition may not contain the dispersant B, or may contain a different type of dispersant B from the dispersant A. The dispersant B contained in the electrode coating liquid composition can be one or more types.
[0085] In the coating liquid composition for an electrode, the content of dispersant B (excluding the polyurethane resin in the polyurethane resin aqueous dispersion) can be the same as that of known coating liquid compositions for an electrode, and can be, for example, 0.01 mass% or more, preferably 0.05 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.2 mass% or more, and particularly preferably 0.3 mass% or more, and can be 5 mass% or less, preferably 3 mass% or less, more preferably 2.5 mass% or less, even more preferably 2 mass% or less, and particularly preferably 1.5 mass% or less, relative to the solid content in the coating liquid composition for an electrode.
[0086] (Other ingredients) The electrode coating liquid composition may also contain a surfactant. Examples of the surfactant include a wide range of surfactants contained in known electrode coating liquid compositions, and may be any of a nonionic surfactant, an anionic surfactant, and a cationic surfactant.
[0087] Examples of the nonionic surfactant include acetylene glycol-based nonionic surfactants. Examples of the acetylene glycol-based nonionic surfactant include Surfynol 420, Surfynol 423, Surfynol 424, Surfynol 425, Surfynol 440, and Surfynol 465 manufactured by Nissin Chemical Industry Co., Ltd., TRITON (registered trademark) HW-1000 manufactured by Dow Chemical Co., Ltd., Olfin AF-103 and Olfin AF-300 manufactured by Nissin Chemical Industry Co., Ltd., and Antifoam 013A manufactured by Kao Corporation. The nonionic surfactant may be a fluorine-based surfactant or a silicon-based surfactant.
[0088] In the electrode coating liquid composition, the content of the surfactant can be the same as that of known electrode coating liquid compositions, and can be, for example, 0.001 mass% or more, preferably 0.005 mass% or more, more preferably 0.01 mass% or more, even more preferably 0.02 mass% or more, and particularly preferably 0.03 mass% or more, and can be 3 mass% or less, preferably 2 mass% or less, more preferably 1 mass% or less, even more preferably 0.5 mass% or less, and particularly preferably 0.1 mass% or less, relative to the solid content in the electrode coating liquid composition.
[0089] The electrode coating liquid composition may further contain various additives as necessary. Examples of such additives include weather resistance agents, antibacterial agents, antifungal agents, pigments, rust inhibitors, dyes, film-forming assistants, silane coupling agents, antiblocking agents, viscosity adjusters, leveling agents, defoamers, dispersion stabilizers, light stabilizers, antioxidants, ultraviolet absorbers, inorganic fillers, organic fillers, plasticizers, lubricants, and antistatic agents.
[0090] (Electrode Coating Liquid Composition) The electrode coating liquid composition contains a polyurethane resin derived from the electrode binder composition. The content of the polyurethane resin can be 0.5% by mass or more relative to the active material, preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and particularly preferably 7% by mass or more, in order to prevent the electrode coating liquid composition from increasing in viscosity. The content of the polyurethane resin can be 30% by mass or less relative to the active material, preferably 25% by mass or less, more preferably 20% by mass or less, even more preferably 15% by mass or less, and particularly preferably 13% by mass or less, in order to prevent the electrode coating liquid composition from increasing in viscosity.
[0091] The solvent contained in the electrode coating liquid composition is not particularly limited, and may be the same as or different from the solvent contained in the polyurethane resin aqueous dispersion, for example.
[0092] The solid content concentration of the electrode coating liquid composition is not particularly limited, but the higher the solid content concentration, the more active material and the like can be contained, and therefore the binder effect can be enhanced and the electrode performance can be improved. From this viewpoint, the solid content concentration of the electrode coating liquid composition is preferably 40 mass% or more, more preferably 43 mass% or more, even more preferably 45 mass% or more, and particularly preferably 48 mass% or more. The solid content concentration of the electrode coating liquid composition can also be 50 mass% or more. In addition, the solid content concentration of the electrode coating liquid composition is preferably 60 mass% or less, more preferably 55 mass% or less, and even more preferably 53 mass% or less, in terms of the fact that aggregation is unlikely to occur and the coatability is easy to be excellent.
[0093] The viscosity of the electrode coating liquid composition of the present invention at a solid content concentration of 50% by mass is preferably 1000 to 25000 mPa·s, more preferably 2000 to 23000 mPa·s, even more preferably 3000 to 20000 mPa·s, and particularly preferably 3000 to 18000 mPa·s, in terms of being less likely to cause aggregation and having excellent coatability. The viscosity of the electrode coating liquid composition of the present invention means a value measured with a B-type rotational viscometer (25°C, 6 rpm).
[0094] The method for preparing the electrode coating liquid composition of the present invention is not particularly limited, and for example, the same method as the known method for preparing an electrode coating liquid composition can be adopted. For example, the electrode coating liquid composition can be prepared by mixing an active material, a conductive assistant, a dispersant, and an electrode binder composition at a predetermined content ratio. For this mixing, for example, a homodisper, a planetary mixer, a propeller mixer, a kneader, a homogenizer, an ultrasonic homogenizer, a colloid mill, a bead mill, a sand mill, a high-pressure homogenizer, etc. can be used.
[0095] The electrode coating liquid composition of the present invention can be used to form an electrode for a power storage device. For example, the electrode can be formed by applying the electrode coating liquid composition to a current collector to form a coating film. Thus, the electrode for a power storage device contains the solid content of the electrode coating liquid composition. In particular, the electrode coating liquid composition can have a higher solid content concentration than conventional electrode coating liquid compositions, so that the function as a binder is fully exerted and an electrode having excellent properties can be easily formed.
[0096] The method for applying the electrode coating liquid composition of the present invention to a current collector is not particularly limited, and for example, a wide variety of known application methods can be used.
[0097] The type of collector to which the electrode coating liquid composition of the present invention is applied is not particularly limited, and can be widely applied to, for example, positive electrode collectors and negative electrode collectors used in lithium secondary batteries. Examples of the positive electrode collector include aluminum, titanium, stainless steel, nickel, baked carbon, conductive polymers, conductive glass, etc., and examples of the negative electrode collector include copper, stainless steel, nickel, aluminum, titanium, baked carbon, conductive polymers, conductive glass, Al-Cd alloys, etc.
[0098] The electrode for a power storage device obtained by using the electrode coating liquid composition of the present invention can be applied to various power storage devices. The power storage device has an electrode for a power storage device obtained by using the electrode coating liquid composition of the present invention, and therefore has excellent characteristics. Examples of the power storage device include known power storage devices, such as lithium secondary batteries and lithium ion capacitors.
[0099] The configuration of the electricity storage device is not particularly limited, and as long as it has an electrode for an electricity storage device obtained using the electrode coating fluid composition of the present invention, it can have a configuration similar to that of a known electricity storage device, for example.
[0100] An electricity storage device (for example, a lithium secondary battery) can be formed into a cylindrical, coin, square, or any other shape. The basic configuration of the battery is the same regardless of the shape, and the design can be modified according to the purpose.
[0101] In specifying the invention included in the present disclosure, the configurations (properties, structures, functions, etc.) described in each embodiment of the present disclosure may be combined in any manner. In other words, the present disclosure includes all subject matter consisting of all combinations of the configurations that can be combined as described in this specification. EXAMPLES
[0102] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the embodiments of these examples.
[0103] (Production Example 1: Polyurethane resin water dispersion A1) Into a four-neck flask equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen inlet tube, 71.3 parts by mass of polybutadiene polyol (Idemitsu Kosan Co., Ltd., PolybdR-45HT, average hydroxyl value 46.5 mgKOH / g), 4.2 parts by mass of dimethylolpropionic acid, 24.5 parts by mass of dicyclohexylmethane diisocyanate, and 100 parts by mass of methyl ethyl ketone were added. Then, the mixture was reacted at 75°C for 4 hours to obtain a methyl ethyl ketone solution of polyurethane prepolymer. The free isocyanate group content relative to the non-volatile content of this methyl ethyl ketone solution was 2.5%. Next, after cooling this solution to 45°C, emulsification and dispersion were performed as follows. 186 parts by mass of water in which 1.25 parts by mass of sodium hydroxide was dissolved was added to the methyl ethyl ketone solution at a rate of 1 part by mass / min (0.67 x 10 in terms of alkali component). -2The mixture was added at a rate of 1.6 parts by mass / min using a homogenizer to emulsify and disperse the mixture, and then 114 parts by mass of water was added to further emulsify and disperse the mixture. An aqueous solution of 1.6 parts by mass of ethylenediamine dissolved in 24 parts by mass of water was added to the resulting emulsion dispersion, and a chain extension reaction was carried out for 1 hour. Thereafter, the reaction solvent methyl ethyl ketone was distilled under reduced pressure at 50°C to obtain a polyurethane resin aqueous dispersion A1 having a solid content concentration of 30% by mass.
[0104] (Production Example 2: Polyurethane resin water dispersion A2) The methyl ethyl ketone solution was diluted with 150 parts by mass of water containing 1.25 parts by mass of sodium hydroxide at a rate of 1 part by mass / min (0.83×10 in terms of the alkali component). -2 A polyurethane resin water dispersion A2 having a solids concentration of 30 mass% was obtained in the same manner as in Production Example 1, except that the mixture was added at a rate of 100 parts by mass / min while being emulsified and dispersed using a homogenizer, and then 150 parts by mass of water was added to further emulsify and disperse the mixture.
[0105] (Production Example 3: Polyurethane resin water dispersion A3) The methyl ethyl ketone solution was diluted with 450 parts by mass of water containing 1.25 parts by mass of sodium hydroxide at a rate of 3 parts by mass / min (0.83×10 in terms of the alkali component). -2 A polyurethane resin water dispersion A3 having a solids concentration of 30 mass% was obtained in the same manner as in Production Example 1, except that the mixture was added at a rate of 100 parts by mass / min while being emulsified and dispersed using a homogenizer, and then 150 parts by mass of water was added and emulsified and dispersed.
[0106] (Production Example 4: Polyurethane resin water dispersion A4) A polyurethane resin water dispersion A4 having a solid content concentration of 30 mass % was obtained in the same manner as in Production Example 1, except that the polybutadiene polyol was changed to hydrogenated polybutadiene polyol (manufactured by Nippon Soda Co., Ltd., NISSO-PB GI-2000).
[0107] (Production Example 5: Polyurethane resin water dispersion A5) The methyl ethyl ketone solution was diluted with 300 parts by mass of water containing 1.25 parts by mass of sodium hydroxide at a rate of 6 parts by mass / min (2.4×10 in terms of the alkali component). -2 A polyurethane resin aqueous dispersion A3 having a solids concentration of 30 mass % was obtained in the same manner as in Production Example 1, except that emulsification and dispersion were carried out using a homogenizer while the aqueous dispersion was added at a rate of 100 parts by mass per minute.
[0108] (Production Example 6: Polyurethane resin water dispersion A6) In order to obtain an aqueous dispersion of polyurethane resin having a 50% cumulative particle size of less than 0.01 μm and a 90% cumulative particle size of 0.1 to 0.15 μm, 122 parts by mass of water in which 1.25 parts by mass of sodium hydroxide was dissolved was added to the methyl ethyl ketone solution at a rate of 1 part by mass / min (1.02×10 in terms of the alkali component). -2 The same method as in Production Example 1 was performed except that 178 parts by mass of water was further added and emulsified and dispersed, while the aqueous polyurethane resin dispersion A6 having a 50% cumulative particle size of less than 0.01 μm was not obtained.
[0109] (Production Example 7: Polyurethane resin water dispersion A7) In order to obtain an aqueous dispersion of polyurethane resin having a 50% cumulative particle size exceeding 0.05 μm and a 90% cumulative particle size of 0.1 to 0.15 μm, 233 parts by mass of water in which 1.25 parts by mass of sodium hydroxide was dissolved was added to the methyl ethyl ketone solution at a rate of 1 part by mass / min (0.54 × 10 in terms of the alkali component). -2 The same method as in Production Example 1 was carried out except that 67 parts by mass of water were added at a rate of 100 parts by mass per minute and emulsified and dispersed using a homogenizer, and then 67 parts by mass of water were added and emulsified and dispersed. However, it was not possible to obtain a polyurethane resin aqueous dispersion A7 in which the 50% cumulative particle size exceeded 0.05 μm.
[0110] (Production Example 8: Polyurethane resin water dispersion A8) The methyl ethyl ketone solution was diluted with 150 parts by mass of water containing 1.25 parts by mass of sodium hydroxide at a rate of 0.5 parts by mass / min (0.42×10 in terms of the alkali component). -2A polyurethane resin water dispersion A8 having a solids concentration of 30 mass% was obtained in the same manner as in Production Example 1, except that the mixture was added at a rate of 100 parts by mass / min while being emulsified and dispersed using a homogenizer, and then 150 parts by mass of water was added to further emulsify and disperse the mixture.
[0111] (Production Example 9: Polyurethane resin water dispersion A9) The methyl ethyl ketone solution was diluted with 150 parts by mass of water containing 1.25 parts by mass of sodium hydroxide at a rate of 6 parts by mass / min (5.0×10 in terms of the alkali component). -2 A polyurethane resin water dispersion A9 having a solids concentration of 30 mass% was obtained in the same manner as in Production Example 1, except that the mixture was added at a rate of 100 parts by mass / min while being emulsified and dispersed using a homogenizer, and then 150 parts by mass of water was added to further emulsify and disperse the mixture.
[0112] [Table 1]
[0113] The results of measuring D50 and D90 of the polyurethane resin water dispersion obtained in each Production Example are shown in Table 1. The polyurethane resin water dispersions obtained in Production Examples 1 to 4 (A1, A2, A3, A4) had a D50 of 0.01 μm or more and 0.05 μm or less, and a D90 of 0.10 μm or more and 0.15 μm or less.
[0114] Example 1 8.5 parts by mass of acetylene black aqueous dispersion (solid content concentration 25% by mass) and 42.9 parts by mass of SWCNT aqueous dispersion (solid content concentration 1.0% by mass) were mixed and stirred for 1 hour, and 48.6 parts by mass of polyurethane resin aqueous dispersion A1 (solid content concentration 30% by mass) obtained in Production Example 1 was added thereto and stirred for 30 minutes to obtain a mixed solution. This mixed solution and 77.4 parts by mass of a carboxymethylcellulose aqueous solution (solid content concentration 1.0% by mass) were stirred with a homodisper for 10 minutes, and then 153.2 parts by mass of active material (SiO) were added and stirred with a homodisper for 10 minutes, and finally 11.6 parts by mass of water were added while stirring, and the solid content was adjusted to obtain an electrode coating liquid composition with a solid content concentration of 50% by mass.
[0115] Example 2 A coating liquid composition for electrodes having a solid content of 50% by mass was obtained in the same manner as in Example 1, except that the polyurethane resin water dispersion A1 was changed to the polyurethane resin water dispersion A2 (solid content concentration: 30% by mass) obtained in Production Example 2.
[0116] Example 3 A coating liquid composition for electrodes having a solid content of 50% by mass was obtained in the same manner as in Example 1, except that the polyurethane resin water dispersion A1 was changed to the polyurethane resin water dispersion A3 (solid content concentration: 30% by mass) obtained in Production Example 3.
[0117] Example 4 A coating liquid composition for electrodes having a solid content of 50% by mass was obtained in the same manner as in Example 1, except that the polyurethane resin water dispersion A1 was changed to the polyurethane resin water dispersion A4 (solid content concentration: 30% by mass) obtained in Production Example 4.
[0118] Comparative Example 1 A coating liquid composition for electrodes having a solid content of 50% by mass was obtained in the same manner as in Example 1, except that the polyurethane resin water dispersion A1 was changed to the polyurethane resin water dispersion A5 (solid content concentration: 30% by mass) obtained in Production Example 5.
[0119] Comparative Example 4 A coating liquid composition for electrodes having a solid content of 50% by mass was obtained in the same manner as in Example 1, except that the polyurethane resin water dispersion A1 was changed to the polyurethane resin water dispersion A8 (solid content concentration: 30% by mass) obtained in Production Example 8.
[0120] Comparative Example 5 A coating liquid composition for electrodes having a solid content of 50% by mass was obtained in the same manner as in Example 1, except that the polyurethane resin water dispersion A1 was changed to the polyurethane resin water dispersion A9 (solid content concentration: 30% by mass) obtained in Production Example 9.
[0121] [Table 2]
[0122] Table 2 shows the viscosity of the electrode coating liquid composition at each solid content prepared in each Example and Comparative Example. From the results in Table 2, the electrode coating liquid composition prepared in the Example had a suppressed increase in viscosity, and in particular, even when the solid content concentration was 50 mass%, the viscosity was at the level of the low solid content concentration region of the electrode coating liquid composition in the Comparative Example. That is, the electrode coating liquid composition prepared in each Example was able to suppress the increase in viscosity of the coating liquid for forming an electrode, and the viscosity was unlikely to increase even if the solid content concentration of the coating liquid was increased. Therefore, it was shown that the electrode binder composition of the present invention is suitable for preparing a coating liquid with a high solid content concentration, and is suitable as a binder component (binding agent) of the electrode coating liquid composition used to manufacture an electrode for a storage device.
Claims
1. A coating liquid composition for an electrode containing a binder composition for an electrode, The solid content is 50% by mass or more and 60% by mass or less, The electrode binder composition is The present invention relates to a polyurethane resin aqueous dispersion, a carbon nanotube, and a carboxymethyl cellulose or a salt thereof. The polyurethane resin has a D50 volume average particle diameter of 0.01 μm or more and 0.05 μm or less, and a D90 volume average particle diameter of 0.10 μm or more and 0.15 μm or less, The content of the carbon nanotubes is 0.1 to 10 parts by mass based on 100 parts by mass of the polyurethane resin, The content of the carboxymethyl cellulose or a salt thereof is 0.1 to 10 parts by mass per 100 parts by mass of the polyurethane resin in the coating liquid composition for an electrode.
2. An electrode for a power storage device, comprising the solids content of the electrode coating liquid composition according to claim 1 .
3. An electricity storage device comprising the electricity storage device electrode according to claim 2 .
Citation Information
Patent Citations
Binder for electrode
JP2013097906A
JPP7161078B